Policy uncertainty and bank stress testing - Paul H. Kupiec (American Enterprise Institute (AEI), 2019)
This paper highlights the policy uncertainty inherent in using stress tests, both to set minimum bank capital requirements and to assess the capital adequacy needed to maintain banking system stability.
Keywords: A; 330; Dodd-Frank Act; federal reserve; stress tests